DNA repair and recovery of RNA synthesis following exposure to ultraviolet light are delayed in long genes - Andrade-Lima, Leonardo C. (Nucleic Acids Res, 2015)
The kinetics of DNA repair and RNA synthesis recovery in human cells following UV-irradiation were assessed using nascent RNA Bru-seq and quantitative long PCR. It was found that UV light inhibited transcription elongation and that recovery of RNA synthesis occurred as a wave in the 5′-3′ direction with slow recovery and TC-NER at the 3′ end of long genes. RNA synthesis resumed fully at the 3′-end of genes after a 24 h recovery in wild-type fibroblasts, but not in cells deficient in transcription-coupled nucleotide excision repair (TC-NER) or global genomic NER (GG-NER). Different transcription recovery profiles were found for individual genes but these differences did not fully correlate to differences in DNA repair of these genes. Our study gives the first genome-wide view of how UV-induced lesions affect transcription and how the recovery of RNA synthesis of large genes are particularly delayed by the apparent lack of resumption of transcription by arrested polymerases.